Boron quantification, concentration mapping and picosecond excitons dynamics in High-Pressure-High-Temperature diamond by cathodoluminescence. (May 2022) - Tappy, Nicolas; Gallo, Pascal; Fontcuberta i Morral, Anna; Monachon, Christian
Abstract: Diamond is one of the most promising materials for high power and extreme conditions electronics. For this to become a reality, incorporation of active dopants needs to be understood. In this article we demonstrate how cathodoluminescence spectroscopy can be used to quantify and spatially map the boron concentration in diamond. We achieve this by probing exciton dynamics outside the steady state using ultrafast electron pulses and time-resolved spectroscopy. The capture lifetime of free excitons by boron allows us to measure the impurity concentration directly, and is selectively sensitive to electrically active dopants. In addition, we update the value of the Auger lifetime of boron-bound excitons in diamond to 185 ± 2 ps. We study different regimes of free and bound excitons dynamics by characterizing different growth sectors of the crystal, with boron concentration varying between 2.8 ⋅ 10 16 and 4.7 ⋅ 10 17 cm − 3 . At higher doping levels, a regime of free-exciton-diffusion-limited relaxation is reached. Overall, this study provides new prospects for the characterization of doping in diamond, by allowing to study impurities incorporation and activation at the microscale and the impact of crystalline defects on the electrical properties, non-destructively and in a self-consistent way. Graphical abstract: Image 1